Mindful eating program (MEPCOP) and its impact on children’s food consumption. - Delgado-Ríos, Myriam; De Lara Pérez, Beatriz; García Fernández, Fernando Javier (Springer, 2025)
Childhood obesity has increased rapidly, and although some studies suggest that mindful eating programs could help address this issue, research on mindfulness-based interventions to improve children’s eating habits remains limited. The goal of this study is to introduce a prevention program based on mindful eating practices aimed at promoting healthy eating behaviors among primary school students (ages 6–11). It also aims to evaluate the intervention’s effectiveness by examining whether the intervention group shows improved adherence to the Mediterranean diet—specifically, reducing sweets and processed foods and increasing fruit and vegetable intake—compared to a control group. The program includes eight classroom sessions and utilizes a mindful tablecloth and a children’s story as key resources. The study employs a pre-test/post-test design with a follow-up phase. Results indicate that this mindful eating program has positive effects on promoting healthier eating habits, increasing fruit and vegetable consumption, and reducing intake of sweets. Findings suggest that incorporating mindful eating into school programs can effectively encourage healthier dietary behaviors and overall well-being among children.
https://openpolicyfinder.jisc.ac.uk/id/publication/15760
Keywords: Terapia de atención plena; Obesidad - Prevención; Niños - Alimentación; Mindfulness; Promotion; Mediterranean diet; Minors; Obesity; Prevention